EPA/DHA and Vitamin A Supplementation Improves Spatial Memory and Alleviates the Age-related Decrease in Hippocampal RXRγ and Kinase Expression in Rats - Létondor, Anne; Buaud, Benjamin; Vaysse, Carole; Richard, Emmanuel; Layé, Sophie; Pallet, Véronique; Alfos, Serge (Frontiers in Aging Neuroscience, 2016)
Studies suggest that eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and vitamin A are critical to delay aged-related cognitive decline. These nutrients regulate gene expression in the brain by binding to nuclear receptors such as the retinoid X receptors (RXRs) and the retinoic acid receptors (RARs). Moreover, EPA/DHA and retinoids activate notably kinase signaling pathways such as AKT or MAPK, which includes ERK1/2. This suggests that these nutrients may modulate brain function in a similar way. Therefore, we investigated in middle-aged rats the behavioral and molecular effects of supplementations with EPA/DHA and vitamin A alone or combined. 18-month-old rats exhibited reference and working memory deficits in the Morris water maze, associated with a decrease in serum vitamin A and hippocampal EPA/DHA contents. RARα, RXRβ, and RXRγ mRNA expression and CAMKII, AKT, ERK1/2 expression were decreased in the hippocampus of middle-aged rats. A combined EPA/DHA and vitamin A supplementation had a beneficial additive effect on reference memory but not in working memory in middle-aged rats, associated with an alleviation of the age-related decrease in RXRγ, CAMKII, AKT, and ERK1 expression in the hippocampus. This study provides a new combined nutritional strategy to delay brain aging.